Myofascial Pain Syndrome Focused on the Upper Trapezius Muscle: A Comparative Randomized Controlled Trial of the Court-Type Traditional Thai Massage versus the Thai Hermit - Jurairat Boonruab PhD; Phiyaphon Poonsuk MSc; Watchara Damjuti PhD; Wichit Supamethangkura MD (SAGE Publishing, 2021)
Myofascial pain syndrome is a common problem that can develop at any age. This study compares the efficacy of the court-type traditional Thai massage (CTTM) to the Thai hermit exercise (THE) in improving the cervical range of motion (CROM) and reducing pain in the upper trapezius muscle. In this study, 46 patient subjects were randomized into 2 groups, with 1 group administered CTTM and the other administered THE. Prior to and following the experiment, their demographic characteristics, pain levels and CROM were measured using a visual analog scale (VAS) and a goniometer, respectively. Data was then analyzed using descriptive statistics, percentage, mean, and standard deviation, as well as inferential statistics. The findings indicate that subjects in both groups demonstrated significantly lower pain and significantly better CROM (P < 0.05). In terms of comparative treatment between the CTTM and THE groups, the results were not found to differ in the range of motion, but a clear difference in pain level measured by VAS was found, in which CTTM provides a better way of reducing pain at the trigger point than THE (P < 0.05). From the findings, it can be concluded that both CTTM and THE are comparably efficacious therapies for myofascial pain in the upper trapezius muscle.